METHODOLOGIES TO STUDY THE BEHAVIOR OF HERBICIDES ON PLANTS AND THE SOIL USING RADIOISOTOPES - MENDES,K.F. (2017)
ABSTRACT In Brazil, the “Pesticide Act” (Act no. 7,802/89) has introduced new criteria related to the environment, public health and agronomic performance in the analyses of pesticide-related activities. Likewise, radioisotopes are used for environmental behavior and in planta studies, since they provide some advantages in comparison to chemical measures, including greater sensitivity, stepwise description of a particular element in a metabolic system, and pesticide position and detection through X-ray films and/or radio image (in plants) and liquid scintillation (in plants and soil), respectively. This review describes methodologies related to radioisotope utilization in studies on herbicide absorption, translocation and metabolism in plants, as well as in studies on herbicide biodegradation, mineralization, leaching and sorption-desorption on the soil. The step-by-step of the described methodologies is based on the guidelines that were established, mostly by the Organization for Economic Co-operation and Development (OECD) and the Environmental Protection Agency (EPA). On this review, methodological information on soil and plant studies, using radioisotopes, is available to Brazilian researchers. Thus, the objective of this review is to stimulate the conduction of further studies that use the methodologies described herein.